Análisis para la Implementación del Sistema Mobile Device Management (MDM), para la Mejora y Control de Acceso, para Garantizar la Seguridad de los Datos de los Estudiantes de la Universidad Técnica de Babahoyo. - Yánez Izquierdo, Indira Daniela (2024)
The present study focuses on the analysis for the implementation of the Mobile Device Management (MDM) System at the Technical University of Babahoyo, with the objective of improving access control and guaranteeing the security of student data. Through a comprehensive methodological approach ranging from initial diagnosis to continuous evaluation, existing challenges in mobile device management were identified and specific strategies were designed to address them. An appropriate MDM solution was selected and implemented, robust security policies were established, and staff and end users were trained. The results obtained show a significant improvement in access control, strengthening of data security and a positive perception by users. It is recommended to maintain continuous monitoring, offer periodic training, keep the system updated and ensure regulatory compliance to ensure the long-term effectiveness of the MDM at the university.